Genetic counseling for deafness - Braga, Maria Cristina C. (Revista de Medicina, 2001)
Congenital deafness is a condition with an astonishing degree of genetic heterogeneity. Using our own data as well as those from selected publications in the national and international literature, we estimated the incidence of the defect, the frequencies of environmental and genetic cases, and the relative frequencies of the different monogenic mechanisms among hereditary cases. All these estimates were used for calculating recurrence risks in many situations arising in the practice of genetic counseling. The risks, calculated for geographic regions with low and high levels of economic and sanitary development, which exhibit a varying degree of environmental and genetic causes, are presented in table form for direct use.